Hydrogen-bond-mediated structural variation of metal guanidinium formate hybrid perovskites under pressure. (15th July 2019) - Yang, Zhengqiang; Cai, Guanqun; Bull, Craig L.; Tucker, Matthew G.; Dove, Martin T.; Friedrich, Alexandra; Phillips, Anthony E.
Abstract : The hybrid perovskites are coordination frameworks with the same topology as the inorganic perovskites, but with properties driven by different chemistry, including host-framework hydrogen bonding. Like the inorganic perovskites, these materials exhibit many different phases, including structures with potentially exploitable functionality. However, their phase transformations under pressure are more complex and less well understood. We have studied the structures of manganese and cobalt guanidinium formate under pressure using single-crystal X-ray and powder neutron diffraction. Under pressure, these materials transform to a rhombohedral phase isostructural to cadmium guanidinium formate. This transformation accommodates the reduced cell volume while preserving the perovskite topology of the framework. Using density-functional theory calculations, we show that this behaviour is a consequence of the hydrogen-bonded network of guanidinium ions, which act as struts protecting the metal formate framework against compression within their plane. Our results demonstrate more generally that identifying suitable host–guest hydrogen-bonding geometries may provide a route to engineering hybrid perovskite phases with desirable crystal structures. This article is part of the theme issue 'Mineralomimesis: natural and synthetic frameworks in science and technology'.